Evaluating current strategies in Response to burglary at residential premises - Nokukhanya Neptune Mbonambi; Shanta Balgobind Singh (The Institute of Academic Research and Publication (IARP), 2023)
It is in the best interest of the South African Police Services (SAPS) to assess the effectiveness of the current strategies which they are employing to respond to burglaries at residential premises in South Africa, this knowledge would assist in addressing burglaries more effectively in the future. This study aimed to contribute to this knowledge by evaluating the current strategies which the SAPS in the Newlands East policing precinct are utilizing to respond to burglaries in the study area. This was deemed necessary as residential burglary had been reported as the highest property-related crime in the study area for the five years (2015-2019) preceding the study. In ensuring that the aim of this study was achieved, the qualitative research design was used, which assisted the researcher to focus on exploring the views of the SAPS members on the current strategies they are employing to respond to burglaries. Data collection for this study was based on semi-structured interviews conducted on an individual basis with selected participants. It combined a set of pre-determined questions that enabled the interviewer to explore further particular themes and responses. The findings of this study revealed that the South African Police Service as well as the Community Policing Forum in the study area have implemented some viable strategies to combat burglary at residential premises. However, these strategies are not entirely effective due to limited manpower and limited vehicles allocated to the police station. These findings suggest that there is an urgent need for the government to intervene by increasing the SAPS budget so that more vehicles and manpower may be deployed to local police stations. This would assist the SAPS to effectively respond to burglaries at residential premises in the study area.